Mars Science Laboratory relative humidity observations: Initial results. Issue 9 (26th September 2014) - Harri, A.‐M.; Genzer, M.; Kemppinen, O.; Gomez‐Elvira, J.; Haberle, R.; Polkko, J.; Savijärvi, H.; Rennó, N.; Rodriguez‐Manfredi, J. A.; Schmidt, W.; Richardson, M.; Siili, T.; et al.
Abstract The Mars Science Laboratory (MSL) made a successful landing at Gale crater early August 2012. MSL has an environmental instrument package called the Rover Environmental Monitoring Station (REMS) as a part of its scientific payload. REMS comprises instrumentation for the observation of atmospheric pressure, temperature of the air, ground temperature, wind speed and direction, relative humidity (REMS‐H), and UV measurements. We concentrate on describing the REMS‐H measurement performance and initial observations during the first 100 MSL sols as well as constraining the REMS‐H results by comparing them with earlier observations and modeling results. The REMS‐H device is based on polymeric capacitive humidity sensors developed by Vaisala Inc., and it makes use of transducer electronics section placed in the vicinity of the three humidity sensor heads. The humidity device is mounted on the REMS boom providing ventilation with the ambient atmosphere through a filter protecting the device from airborne dust. The final relative humidity results appear to be convincing and are aligned with earlier indirect observations of the total atmospheric precipitable water content. The water mixing ratio in the atmospheric surface layer appears to vary between 30 and 75 ppm. When assuming uniform mixing, the precipitable water content of the atmosphere is ranging from a few to six precipitable micrometers.